Monetary economics an integrated approach to credit, money, income, production and wealth - Godley, Wynne 1926-2010; Lavoie, Marc 1954- (Palgrave Macmillan, 2012)
This book challenges the mainstream paradigm, which is based on the inter-temporal optimisation of welfare by individual agents. It introduces a new methodology for studying how it is institutions which create flows of income, expenditure and production together with stocks of assets (including money) and liabilities, thereby determining how whole economies evolve throughtime. Starting with extremely simple stock flow consistent (SFC) models, the text describes a succession of increasingly complex models. Solutions of these models are used to illustrate ways in which whole economiesevolve when shocked in various ways. Readers will be able to downloadall the models and explore their properties for themselves. A major conclusion is that economies require management via fiscal and monetary policyif full employment without inflation is to be achieved.
Includes bibliographical references and index
Keywords: Monetarisme; Mathematisches Modell; Wirtschaft; Money; Economics -- Mathematical models; Makroökonomie; Geldtheorie; Offene Volkswirtschaft